Prediction of small-for-gestational age by fetal growth rate according to gestational age. - Min-A Kim; Gwan Hee Han; Young-Han Kim (PLoS ONE, 2019)
Background Small-for-gestational age (SGA) infants should be identified before birth because of an increased risk of adverse perinatal outcomes. The objective of this study was to assess the impact of fetal growth rate by gestational age on the prediction of SGA and to identify the optimal time to initiate intensive fetal monitoring to detect SGA in low-risk women. We also sought to determine which the ultrasonographic parameters that contribute substantially to the birthweight determination. Methods This was a retrospective study of 442 healthy pregnant women with singleton pregnancies. There were 328 adequate-for-gestational age (AGA) neonates and 114 SGA infants delivered between 37+0 and 41+6 weeks of gestation. We compared the biparietal diameters (BPD), head circumferences (HC), abdominal circumferences (AC), femur lengths (FL), and estimated fetal weights (EFW) obtained on each ultrasound to determine which of these parameters was the best indicator of SGA. We created receiver operating characteristic curves, calculated the areas under the curves (AUCs), and analyzed the data using multivariable logistic regressions to assess the ultrasound screening performances and identify the best predictive factor. Results Among the four ultrasonographic parameters, the AC measurement between 24+0~28+6 weeks achieved a sensitivity of 79.5% and a specificity of 71.7%, with an AUC of 0.806 in the prediction of SGA. AC showed consistently higher AUCs above 0.8 with 64~80% sensitivities as gestational age progressed. EFW measurements from 33+0~35+6 gestational weeks achieved a sensitivity of 60.6% and a specificity of 87.6%, with an AUC of 0.826. In a conditional growth model developed from the linear mixed regression, the value differences between AC and EFW in the SGA and AGA groups became even more pronounced after 33+0~35+6 weeks. Conclusion Healthy low-risk women with a low fetal AC after 24 weeks' gestation need to be monitored carefully for fetal growth to identify SGA infants with a risk for adverse perinatal outcomes.